Advances in Biosynthesis of Nanoparticles: A Review - Ismail, Rusul K.; Al Hussan, Shahlaa M. Abd; Jasim, Saif Khalel (Indonesian Journal of Material Research, 2025)
This paper provides a detailed review of nanoparticle biosynthesis, highlighting biological synthesis methods in comparison to physical and chemical approach. It addresses the shortcomings of existing techniques and explores potential advancements in this field. And, the applications of the nanoparticles prepared in a biological in the medical field, as well as studying its advantages and disadvantages, were highlighted. The paper review also provides a brief overview of nanoparticle applications, linking them to both the desired and achieved sizes through various synthesis methods.